Public Policy and Extended Families : Evidence from Pensions in South Africa - Bertrand, Marianne; Mullainathan, Sendhil; Miller, Douglas (Washington, DC: World Bank, 2014)
How are resources allocated within extended families in developing economies? This question is investigated using a unique social experiment: the South African pension program. Under that program the elderly receive a cash transfer equal to roughly twice the per capita income of Africans in South Africa. The study examines how this transfer affects the labor supply of prime-age individuals living with these elderly in extended families. It finds a sharp drop in the working hours of prime-age individuals in these households when women turn 60 years old or men turn 65, the ages at which they become eligible for pensions. It also finds that the drop in labor supply is much larger when the pensioner is a woman, suggesting an imperfect pooling of resources. The allocation of resources among prime-age individuals depends strongly on their absolute age and gender as well as on their relative age. The oldest son in the household reduces his working hours more than any other prime-age household member.